EFFECT OF MURRAYA KOENIGII AND AEGLE MARMELOS FEEDING ON ANES.TRUS BUFFALOES - DUTT, RAVI; MEHROTRA, S; SHANKER, UMA; SINGH, GYANENDRA (The Indian Journal of Animal Reproduction, 2011)
The study was conducted to examine the effect of combination treatment of Murraya koenigii and Aegle marmelos on restoration of fertility in anestrus buffaloes. Effective 50% ethanolic extract doses of both the plants were extrapolated from rats (1000 mg/kg) to buffaloes using dose equivalent system and converted into powder form based on per-cent yield. Final doses were prepared by mixing of half of the calculated dose of both the plants on body weight bjisis. Twenty anestrus b!Jffaloes of 4-7 years age were divided into two equal groups i.e. control (I) and treatment (II). Animals of treatment group were treated with leaves powder orally for nine days against untreated control. Estrus was induced in 60% (6/10) animals in group II with a mean interval of 9.33±1.11 days from end of experiment followed by 66.67% (4/6) pregnancy confirmation on day 45 post mating. Results indicated favourable effect of plants combination on reproductive function, under anestrus condition in buffaloes.